2009
DOI: 10.1590/s0100-40422009000500033
|View full text |Cite
|
Sign up to set email alerts
|

Peptídeos cíclicos de biomassa vegetal: características, diversidade, biossíntese e atividades biológicas

Abstract: Recebido em 7/4/08; aceito em 23/9/08; publicado na web em 30/4/09 CYCLIC PEPTIDE FROM PLANT BIOMASS: CHEMICAL FEATURES AND DIVERSITY, BIOSYNTHESIS AND BIOLOGICAL ACTIVITIES. Natural peptides are outstanding as the most promising macromolecules in the search for new drugs, especially those of cyclic nature. The higher plants revealed a very peculiar composition of their cyclic peptides, which distinguish themselves by a "head-to-tail" cyclization. It is possible to define two groups of cyclic peptides from pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 83 publications
0
15
0
4
Order By: Relevance
“…CPs belonging to the Caryophyllaceae group consist of 7-10 aminoacids with a high proportion of hydrophobic residues [8][9][10][11][12] being recently named as Orbitide [13]. Biobollein (9 residues) and Labaditin (10 residues), isolated from Jatropha Multifida, were the first CPs of this group of peptides described in the literature [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…CPs belonging to the Caryophyllaceae group consist of 7-10 aminoacids with a high proportion of hydrophobic residues [8][9][10][11][12] being recently named as Orbitide [13]. Biobollein (9 residues) and Labaditin (10 residues), isolated from Jatropha Multifida, were the first CPs of this group of peptides described in the literature [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The enhancer activity however, reserved to the cyclic form (Cp), should be supported, as least in part, by the higher resistance to enzymatic hydrolysis in a medium highly hydrolytic. Even, in linear sequences ending points are suitable sites of recognition for degradation that does not occur in closed sequences [21,28]. Therefore our proposal remains to be probed.…”
Section: Biological Functions and Applicationsmentioning
confidence: 95%
“…Many reports in literature have showed that linear and cyclic peptides exhibit functional differences which are attributed to its individual structural arrangement [21]. For this reason, both synthetic peptides, linear (1341.36 g/mol) and cyclic (1323.19 g/mol), designed on the APTLSGGSVPRDAD sequence, were acquired and studied.…”
Section: Structural Analyses Of Synthetic Analoguesmentioning
confidence: 99%
“…They have been documented in families including Annonaceae, Euphorbiaceae, Lamiaceae, Linaceae, Phytolaccaceae, Rutaceae, Schizandraceae and Verbenaceae. [2][3][4][5] In recent decades, the Jatropha genus (Euphorbiaceae family) has emerged as a rich source of bioactive orbitides. 5,6 Plants from this genus are endemic in the Brazilian semi-arid region (Caatinga biome) 7 and represent a popularly known source of toxins and medicines.…”
Section: Introductionmentioning
confidence: 99%